2023
DOI: 10.3390/nu15163664
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Models and Cardiovascular Risk Prevention in Pediatric Patients

Maria Capra,
Delia Monopoli,
Nicola Decarolis
et al.

Abstract: Nutritional intervention is worldwide recognized as a first step treatment for subjects with increased cardiovascular risk and it is of utmost importance especially for children and adolescents. Currently scientific evidence supports the role of dietary patterns instead of simple single nutrients or foods in cardiovascular risk prevention. Indeed, the American Heart Association dietary guidelines have expanded beyond nutrients to dietary pattern, that comprise not only single food items but also behavioral or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 165 publications
0
4
0
Order By: Relevance
“…National and international guidelines [ 18 , 23 , 48 ] promote a CF based on a wide variety of CFs. However, plant-based diets (e.g., vegetarian and vegan diets) are also gaining popularity [ 65 ] among parents, who often ask pediatricians to provide their children with CF based on such dietary regimes [ 66 ]. Due to the paucity of robust data supporting the feasibility and safety of these alternative CF regimens in the PI population, they should be carefully planned by a nutrition expert professional, who should recommend the consumption of foods rich in iodine, zinc, iron, calcium, and LCPUFAs, and low in fiber.…”
Section: Traditionmentioning
confidence: 99%
See 1 more Smart Citation
“…National and international guidelines [ 18 , 23 , 48 ] promote a CF based on a wide variety of CFs. However, plant-based diets (e.g., vegetarian and vegan diets) are also gaining popularity [ 65 ] among parents, who often ask pediatricians to provide their children with CF based on such dietary regimes [ 66 ]. Due to the paucity of robust data supporting the feasibility and safety of these alternative CF regimens in the PI population, they should be carefully planned by a nutrition expert professional, who should recommend the consumption of foods rich in iodine, zinc, iron, calcium, and LCPUFAs, and low in fiber.…”
Section: Traditionmentioning
confidence: 99%
“…Furthermore, some people follow a primary plant diet (similar to lacto-ovo-vegetarian but with small amounts of lean meat) or pescatarian (which excludes meat and poultry, while fish is permitted). There are also some very restrictive subtypes, such as raw vegan diet (all cooked foods and processed foods are excluded), fruitarian diet (only fruits, nuts, and seeds are permitted), and macrobiotic diet (based on Taoist “yin and yang” principles, which emphasize whole grains, beans, and vegetables) [ 65 , 89 ]. The Italian Position Paper on Vegetarian Diets in Pregnancy and Developmental Age states that there is yet not enough scientific evidence to determine at what age it is safe to start a vegetarian diet.…”
Section: Plant-based Complementary Feedingmentioning
confidence: 99%
“…To meet these higher needs, infants' and toddlers' nutrition typically requires a high lipid intake (35-45% of total daily energy intake) [17], as provided by human milk, which remains the gold standard food, even for infants with severe hypercholesterolemia [16]. Human milk, indeed, provides more cholesterol than any formula milk, but it has been demonstrated that it serves as a positive epigenetic factor, playing a preventive and protective role against the development of hypercholesterolemia [18], blood hypertension [19], obesity [20], and eating disorders (both in terms of quantity of foods and on preference for healthier foods) [21,22] later in life. Complementary feeding (formerly defined as weaning) corresponds to the introduction of solid foods, typically offering lower lipid and higher carbohydrate and protein contents when neither human nor formula milk intake can sufficiently meet the macro and micronutrients needs of infants.…”
Section: Lipid Restrictionmentioning
confidence: 99%
“…Several problems, particularly in adolescents and young adults, emerged. Together with several mental symptoms as well as anxiety, stress, depression, event-specific distress, decrease in psychological wellbeing, and changes in sleep habits [5], the limitation of physical activity and practicing sports led to an increased incidence of overweight, obesity and metabolic syndromes associated with a greater risk of cardiovascular diseases [6][7][8][9][10]. When public health policies progressively reduced limitations and resuming a normal life was possible, the return to previous physical activity and sports was not only requested by people who had deeply suffered from limitations, but was also recommended by experts as a means of reducing the physical and psychological consequences induced by the pandemic [11][12][13].…”
Section: Introductionmentioning
confidence: 99%